2021
DOI: 10.1186/s12199-021-00942-4
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor air pollution and diminished ovarian reserve among infertile Korean women

Abstract: Background Mounting evidence implicates an association between ambient air pollution and impaired reproductive potential of human. Our study aimed to assess the association between air pollution and ovarian reserve in young, infertile women. Methods Our study included 2276 Korean women who attended a single fertility center in 2016–2018. Women’s exposure to air pollution was assessed using concentrations of particulate matter (PM10 and PM2.5), nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…18,20 Epidemiologic studies have shown that air pollution exposure may diminish ovarian reserve. [59][60][61] In addition, epidemiologic studies of couples undergoing in vitro fertilisation can inform underlying mechanisms, as each step in the reproductive process is observed and measured. For instance, in a cohort of 357 women undergoing fertility treatment at a Massachusetts hospital, associations between traffic-related air pollutants were strongest early in the IVF cycle, specifically before embryo transfer.…”
Section: Discussionmentioning
confidence: 99%
“…18,20 Epidemiologic studies have shown that air pollution exposure may diminish ovarian reserve. [59][60][61] In addition, epidemiologic studies of couples undergoing in vitro fertilisation can inform underlying mechanisms, as each step in the reproductive process is observed and measured. For instance, in a cohort of 357 women undergoing fertility treatment at a Massachusetts hospital, associations between traffic-related air pollutants were strongest early in the IVF cycle, specifically before embryo transfer.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of these air pollutants on fertility, birth weight, preterm birth, and the presence of congenital anomalies was investigated (Table 1, Ref. [3,20,22,23,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]: Summary of the effects of air pollution on pregnancy) [25].…”
Section: Impact Of Air Pollutant Exposure On Pregnancymentioning
confidence: 99%
“…Exposure to PM 2.5 and PM 10 is also inverse associated with anti-müllerian hormone (AMH), a in indicator of ovarian reserve [27,28].…”
Section: Particulate Matter and Fertilitymentioning
confidence: 99%
“…15 Several studies have demonstrated that increased exposure to fine particulate matter was associated with lower ovarian reserve markers. 16 , 17 , 18 , 19 A cross-sectional study based on 67 women residing in Sabzevar, Iran revealed a detrimental association of exposure to PM 1 and PM 2.5 with serum levels of AMH. 19 Another study by Hood et al (2021) included 565 women seeking infertility evaluation and treatment and reported that higher exposure to PM 2.5 was associated with lower AFC.…”
Section: Introductionmentioning
confidence: 99%